Geometrical Methods for Power Network Analysis - Bellucci, Stefano; Tiwari, Bhupendra Nath; Gupta, Neeraj (SpringerBriefs in Electrical and Computer Engineering, 2013)
This book is a short introduction to power system planning and operation using advanced geometrical methods. The approach is based on well-known insights and techniques developed in theoretical physics in the context of Riemannian manifolds. The proof of principle and robustness of this approach is examined in the context of the IEEE 5 bus system. This work addresses applied mathematicians, theoretical physicists and power engineers interested in novel mathematical approaches to power network theory.